Cementation of structures for zirconia-based fixed partial dentures - Echeverri-Palomino, Diana Margarita; Garzón-Rayo, Herney (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Thanks to the nature of zirconia, modern dentistry is now provided with a material that offers good esthetic results, biocompatibility, and effective resistance to masticatory loads for ceramic structures in fixed dentures. However, such nature also has a limitation: poor adhesive properties, which limits certain clinical applications and inhibits the advantages of adhesive bonding, such as improved retention, prevention of micro-leakage, and increased resistance to fracture and fatigue. This article reviews some of the issues related to the cementation protocols commonly used for structures in zirconia fixed dentures on natural teeth, their results over time, and recent studies on treatment possibilities for zirconia surfaces. No conclusive literature exists so far to support the superiority of the adhesive bonding properties of zirconia over conventional cementation; furthermore, no clinical studies are available to support the effectiveness and durability of the new protocols proposed to produce roughness and to chemically activate zirconia surfaces.